Factors Influencing Performance of SACCOS in Kenya: A Case of UNAITAS SACCO - Mwangi, Edna; Wambua, Dr. Leonard (European Journal of Business and Strategic Management, 2016)
Purpose: The general objective of this study was to establish factors influencing performance of saccos in Kenya: a case Unaitas Sacco. Methodology: The study adopted a case study where primary data was gathered using the questionnaire. The population of the study was all the senior staff (top, middle and supervisory levels of management). There were total 96 such managers in UNAITAS Sacco. The list was obtained from the human resource department. The sample size was 50% of the population. The sample size was therefore 48 managers. The sampling technique/design was simple random sampling. The researcher used quantitative techniques in analyzing the data. The tool of analysis was SPSS version 20 was used. Descriptive analysis was employed; which included; mean standard deviations and frequencies/percentages. Inferential statistics that was used was correlation and regression analysis. Results: Results of the study indicated that organization subculture, organization structure, organization leadership capacity and organization rewarding practices had a positive and significant effect on the performance. The study concluded that organizational subculture, organizational structure, leadership capacity and rewarding practices had an active and direct role in performance. Unique contribution to theory, practice and policy: The study recommended that the institution should undertake an internal review of the administrative functions that impact the suppression/operations division and identify structure as one the determining factor of performance.